Accelerated tissue integration into porous materials by immobilizing basic fibroblast growth factor using a biologically safe three‐step reaction. Issue 12 (29th June 2015) - Kakinoki, Sachiro; Sakai, Yusuke; Fujisato, Toshia; Yamaoka, Tetsuji
ABSTRACT: Soft tissue integration into a porous structure is important to prevent bacterial infection of percutaneous devices and improve tissue regeneration using porous scaffolds. Here, basic fibroblast growth factor (bFGF) was immobilized on porous polymer materials using a mild and biologically safe three‐step reaction: (1) modification with a novel surface‐modification peptide (penta‐lysine‐mussel adhesive sequence, which reacts with various matrices), (2) electrostatic binding of heparin with introduced penta‐lysine, and (3) biologically specific binding of bFGF to heparin. Porous polyethylene specimens (PPSs) ( D = 6.0 mm, H = 2.0 mm) with a good size for tissue integration were selected as a base material, immobilized with bFGF, and subcutaneously implanted into mice. Half of the unmodified PPSs extruded out of the body on day 112 postimplantation; however, the three‐step reaction completely prevented sample rejection. Tissue integration was greatly accelerated by immobilizing bFGF. Direct physical coating of bFGF on PPS resulted in greater immobilization but lesser tissue integration than that after the three‐step bFGF immobilization, indicating that heparin binds and enhances bFGF efficacy. This three‐step bFGF immobilization reaction will be applicable to various polymeric, metallic, and ceramic materials and is a simple strategy to integrate tissue on porous medical devices or scaffolds for tissue regeneration. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 103A: 3790–3797, 2015.